2014
DOI: 10.1021/am501961b
|View full text |Cite
|
Sign up to set email alerts
|

Building an Antifouling Zwitterionic Coating on Urinary Catheters Using an Enzymatically Triggered Bottom-Up Approach

Abstract: Catheter associated urinary tract infections are common during hospitalization due to the formation of bacterial biofilms on the indwelling device. In this study, we report an innovative biotechnology-based approach for the covalent functionalization of silicone catheters with antifouling zwitterionic moieties to prevent biofilm formation. Our approach combines the potential bioactivity of a natural phenolics layer biocatalytically conjugated to sulfobetaine-acrylic residues in an enzymatically initiated surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 48 publications
2
103
0
1
Order By: Relevance
“…In 2014, Blanco et al found that functionalization of silicone catheters with zwitterionic moieties provided antibiofilm properties to the catheter against P. aeruginosa and S. aureus [175]. The coating was primarily composed of PDMS which was plasma-activated and preaminated.…”
Section: Antimicrobial Urinary Catheter Coating Agents/materials Imentioning
confidence: 99%
“…In 2014, Blanco et al found that functionalization of silicone catheters with zwitterionic moieties provided antibiofilm properties to the catheter against P. aeruginosa and S. aureus [175]. The coating was primarily composed of PDMS which was plasma-activated and preaminated.…”
Section: Antimicrobial Urinary Catheter Coating Agents/materials Imentioning
confidence: 99%
“…Díaz Blanco and co‐workers also employed oxygen plasma to hydroxylate flat poly(dimethylsiloxane) (PDMS; Scheme ) . The hydroxylated surface was then treated with APTES to generate amine‐functionalised PDMS (PDMS‐NH 2 ).…”
Section: Laccase‐mediated Grafting On Synthetic Polymersmentioning
confidence: 99%
“…Water contact angles of dried films in air were measured under ambient conditions (Â amb ) and saturated water vapor conditions (Â sat ) using a sessile drop method. Air contact angles in water (Â air ) were examined for films immersed in water for 30 min before measurements using a captive bubble method [43][44][45]. All measurements were conducted at room temperature.…”
Section: Film Surface Propertiesmentioning
confidence: 99%